An evaluation of bird weight and diet nutrient density during early lay on ISA Brown performance, egg quality, bone characteristics, and liver health at 50 weeks of age - Wendy I. Muir; Yeasmin Akter; Kenneth Bruerton; Peter J. Groves (Poultry Science, 2022)
ABSTRACT: This study compared the impact of a higher nutrient density (HND) or lower nutrient density (LND) diet fed during early lay to either heavier weight (HW) or lighter weight (LW) ISA Brown hens. At 18 wk of age (WOA) pullets (n = 240) were evenly assigned to either HW (n = 120) or LW (n = 120). Sixty birds from each weight group were then randomized to either the HND or LND diet treatments which were fed from 18 to 24 WOA inclusive. At 25 WOA the LND diet replaced the HND diet. All hens remained on LND diet to 50 WOA. Hen performance was measured from 18 to 50 WOA. Femur and liver health were evaluated at 50 WOA. Egg quality was assessed from 46 to 50 WOA. The 18 WOA HW hens had higher BW, cumulative egg production, cumulative feed intake (CFI), and cumulative egg mass (CEM) to both 24 and 50 WOA (P < 0.01). At 24 WOA the HND diet also generated higher BW (P < 0.001), CEM (P < 0.001) and lower cumulative feed conversion ratio (CFCR) (P < 0.01), the latter being sustained to 50 WOA (P < 0.01). At 50 WOA CFCR of LW birds was lower than HW birds (P < 0.01). Egg weight (EW), yolk diameter, and percent yolk weight were higher (P < 0.05) in the HW birds with the highest albumen to yolk ratio in LW birds (P < 0.05). Egg shape index was higher in LND diet fed birds (P < 0.01) while LW hens had higher shell phosphorus (P < 0.05). Body weight and diet nutrient density interacted on femoral diameter and cortical thickness being higher (P < 0.01) in LW birds fed HND than LW birds fed LND diets. Fatty liver hemorrhagic scores (P < 0.05) and liver lipid peroxidase (P < 0.001) at 50 WOA were higher in HW and LND diet treatments. Concurrently HW birds had the highest CFI and EW while CFCR and liver health were superior in LW and the HND diet treatment.